Epitaxy of Semiconductors Introduction to Physical Principles - Pohl, Udo W.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Introduction to Epitaxy provides the essential information for a comprehensive upper-level graduate course treating the crystalline growth of semiconductor heterostructures. Heteroepitaxy represents the basis of advanced electronic and optoelectronic devices today and is considered one of the top fields in materials research. The book covers the structural and electronic properties of strained epitaxial layers, the thermodynamics and kinetics of layer growth, and the description of the major growth techniques metalorganic vapor phase epitaxy, molecular beam epitaxy and liquid phase epitaxy. Cubic semiconductors, strain relaxation by misfit dislocations, strain and confinement effects on electronic states, surface structures and processes during nucleation and growth are treated in detail. The Introduction to Epitaxy requires only little knowledge on solid-state physics. Students of natural sciences, materials science and electrical engineering as well as their lecturers benefit from elementary introductions to theory and practice of epitaxial growth, supported by pertinent references and over 200 detailed illustrations.
Epitaxy -- Structural Properties of Heterostructures -- Electronic Properties of Heterostructures -- Thermodynamics of Epitaxial Layer-Growth -- Atomistic Aspects of Epitaxial Layer Growth -- Doping, Diffusion, and Contacts -- Methods of Epitaxy.
Keywords: Physics; Chemistry, Physical organic; Crystallography; Optical materials; Physics; Semiconductors; Optical and Electronic Materials; Physical Chemistry; Applied and Technical Physics; Crystallography